Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Sikap Keuangan, terhadap Pengelolaan Keuangan UMKM di Kota Sidoarjo melalui Locus of Control sebagai Variabel Intervening - Cahyani, Firlin Eka Kurnia; Supardi, Supardi; Sari, Herlinda Maya Kumala (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the influence of financial literacy, financial inclusion, and financial attitudes on the financial management of MSMEs in Sidoarjo City using locus of control as an intervening variable. This study used quantitative methods. The research sample consisted of 100 respondents and the sampling technique used purposive sampling. The analytical technique used in this study was path analysis. The test results showed a simultaneous positive and significant influence between the variables of financial literacy, financial inclusion, and financial attitudes on the financial management of MSMEs in Sidoarjo City, but partially there was a negative influence between the variables of financial literacy and financial inclusion on financial management. This study also found that the variable of locus of control can intervene in the influence of the variables of financial literacy, financial inclusion, and financial attitudes on the financial management variable of MSMEs in Sidoarjo City.